Shaping the Grammar of Security. (AmeriQuests, 2014)
In Australia, practices of preemptive deterrence construct the political identity of asylum seekers as the ‘illegal other’, and as a threat to national security and to national identity. At the core of the state's illegality regimes lies the endorsement of exclusionary norms through the grammar of security. Who is responsible for the endorsement of these norms and how do they (re)produce illegality regimes? How are securitization moves legitimized and sustained through illegality regimes? How may they be resisted? A case study of Sweden illustrates how the securitization discourses mobilizing illegality regimes may be resisted through norm circles in the political sphere that endorse norms of egalitarianism, justice and equality.This paper focuses on the ‘critical realism’ associated with the works of Dave Elder-Vass and Roy Bhaskar. Elder-Vass draws on the philosophy of Roy Bhaskar to examine the ontology of language, discourse, culture and knowledge and their contribute to the construction of social reality, thus synthesizing aspects of realism and constructionism. Roy Bhaskar’s philosophy of the social sciences has aimed to crystallize a transcendental realist framework incorporating a form of critical naturalism and also critical hermeneutics.